Hypergastrinemia and recurrent type 1 gastric carcinoid in a young Indian male: Necessity for antrectomy? - Senadhi, Viplove (Baishideng Publishing Group Co., Limited, 2011)
Carcinoid tumors are the most common neuroendocrine tumors. Gastric carcinoids represent 2% of all carcinoids and 1% of all gastric masses. Due to the widespread use of Esophagogastroduodenoscopy for evaluating a variety of upper gastrointestinal symptoms, the detection of early gastric carcinoids has increased. We highlight an alternative management of a young patient with recurrent type 1 gastric carcinoids with greater than 5 lesions, as well as lesions intermittently greater than 1 cm. Gastric carcinoids have a variable presentation and clinical course that is highly dependent on type. Type 1 gastric carcinoids are usually indolent and have a metastasis rate of less than 2%, even with tumors larger than 2 cm. There are a number of experts as well as organizations that recommend endoscopic resection for all type 1 gastric carcinoid lesions less than 1 cm, with a follow-up every 6-12 mo. They also recommend antrectomy for type 1 gastric carcinoids with greater than 5 lesions, lesions 1 cm or greater, or refractory anemia. However, the American Society of Gastrointestinal Endoscopy guidelines state that type 1 gastric carcinoid surveillance is controversial based on the evidence and could not make an evidence-based position statement on the best treatment modality. Our report illustrates a rare cause of iron deficiency anemia in a young male (without any medical history) due to multiple recurrent gastric carcinoid type 1 lesions in the setting of atrophic gastritis causing hypergastrinemia, and in the absence of a vitamin B12 deficiency. Gastric carcinoid type 1 can present in young males without an autoimmune history, despite the known predilection for women aged 50 to 70 years. Type 1 gastric carcinoids can be managed by endoscopic resection in patients with greater than 5 lesions, even with lesions larger than 1 cm. This course of treatment enabled the avoidance of early antrectomy in our patient, who expressed a preference against more invasive measures at his young age.